The creative services sector in Polish cities - Radosław Wolniak; Izabela Jonek-Kowalska (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The creative services sector plays an important and constantly growing role in the modern economy. This publication presents the results of extensive research on the functioning of the creative sector in Polish cities, conducted on a representative sample of 287 cities located throughout Poland. The sample was good in such a way as to maintain the structure by province. The survey included questions rated on a 5-point Likert scale. The aim of the research was to study the functioning of the creative sector in Polish cities and to determine whether the active involvement of public administration in its development has a positive impact on this sector. The research was carried out on the example of a medium-sized European country, which is Poland. The original contribution of the authors of the publication is to demonstrate, on a large research sample, the existence of a positive impact of the municipal office's activities on the creative sector for example using special funds to boost creativity sector in the city, and to ascertain the existence of a linear relationship between the city size and the level of the creative sector functioning in it.
Keywords: 650; creative city; creative industry; creativity; innovativeness; public management; quality of life; smart city